A comparison of heat acclimation by post-exercise hot water immersion and exercise in the heat - McIntyre, R. D.; Zurawlew, M. J.; Oliver, S. J.; Cox, A. T.; Mee, J. A.; Walsh, N. P. (Journal of Science and Medicine in Sport, 2021)
Objectives: To compare heat acclimation adaptations after three and six days of either post-exercise hot water immersion (HWI) or exercise-heat-acclimation (EHA) in recreationally active individuals. Design: Randomised, mixed model, repeated measures. Methods: Post-exercise HWI involved a daily 40-min treadmill-run at 65% VO2peak in temperate conditions (19°C, 45% RH) followed by HWI (=40min, 40°C water; n=9). Daily EHA involved a =60-min treadmill-run in the heat (65% VO2peak; 33°C, 40% RH; n=9), chosen to elicit a similar endogenous thermal stimulus to HWI. A thermoneutral exercise intervention (TNE, 19°C, 45% RH; n=9), work-matched to EHA, was also included to determine thermoregulatory adaptations to daily exercise in temperate conditions. An exercise-heat-stress-test was performed before and after three and six intervention days and involved a 40-min treadmill-run and time-to-exhaustion (TTE) at 65% VO2peak in the heat (33°C, 40% RH). Results: ANCOVA, using baseline values as the covariate, revealed no interaction effects but significant group effects demonstrated that compared to EHA, HWI elicited larger reductions in resting rectal temperature (Tre; p=0.021), Tre at sweating onset (p=0.011), and end-exercise Tre during exercise-heat-stress (-0.47°C; p=0.042). Despite a similar endogenous thermal stimulus to HWI, EHA elicited a modest reduction in end-exercise Tre (-0.26°C), which was not different from TNE (-0.25°C, p=1.000). There were no main effects or interaction effects for end-exercise Tsk, heart rate, physiological strain index, RPE, thermal sensation, plasma volume, or TTE (all p=0.154). Conclusions: Compared with conventional short-term exercise heat acclimation, short-term post-exercise hot water immersion elicited larger thermal adaptations.